2015
DOI: 10.18857/jkpt.2015.27.3.169
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Repetitive Sit-to-Stand Training with a Pareticside Asymmetrical Foot Position on the Balance of Chronic Stroke Subjects

Abstract: This study aimed to improve the asymmetrical weight-bearing ratio, by applying different repetitive sit-to-stand training methods to the paretic-side foot of hemiplegic patients, as well as to provide the necessary information for applying balance training with hemiplegic patients. Methods: The subjects were divided into two groups: a spontaneous foot group and an asymmetrical foot group. They all performed repetitive sit-to-stand training five times a week for a total of six weeks. The sit-to-standing movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results of this study are opposite to the present study which showed that equal weight bearing sit to stand has efficacy in improving balance in stroke patients. Contradictory to the findings of our study Park, 13 found that the repetitive sit-to-stand training is significant in asymmetrical Group showed increases in static and dynamic balance in comparison to the spontaneous Group. Conflicting results obtained in another study.…”
Section: Discussionsupporting
confidence: 67%
“…The results of this study are opposite to the present study which showed that equal weight bearing sit to stand has efficacy in improving balance in stroke patients. Contradictory to the findings of our study Park, 13 found that the repetitive sit-to-stand training is significant in asymmetrical Group showed increases in static and dynamic balance in comparison to the spontaneous Group. Conflicting results obtained in another study.…”
Section: Discussionsupporting
confidence: 67%
“…Significant differences were observed in the COP displacement distance and velocity among the four groups ( p < 0.05). Park et al [ 31 ] conducted a study on patients with stroke involving feedback training based on foot position, in which the COP displacement decreased from 241 to 188 mm, whereas the COP mean velocity decreased from 25 to 13 mm/s. Therefore, there was a significant improvement in balance ability before and after the intervention in the experimental group compared to the control group ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…After 3 times of measurements, the stability index is calculated with the average value. [4,27] 2.3.2. Timed Up and Go (TUG) test.…”
Section: Experimental Instrumentationmentioning
confidence: 99%